Typologies for targeting private sector investments in gender equality and social inclusion in agrifood supply chains: A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Soto, Fernanda; Shijagurumayum, Meghajit; Elias, Marlene; Wiegel, Jenny; Morgan, Miranda; Nguyen Perperidis, Emily; Ronchi, Loraine (2025)
Tool 1 in the Gender Transformative Research Methodologies Toolkit. When private-sector actors gain a clearer understanding of who participates in value chains and the diverse experiences, benefits, and challenges they face, they are better equipped to design and implement effective and equitable strategies that advance gender equality, women’s empowerment, and social inclusion—while strengthening value chain sustainability and contributing to long-term business competitiveness and profitability. Main focus on organizations.